The Future Challenge of Climatic Refugees Regional Developments Case study: South Khorasan - Issa Ebrahimzadeh; morteza esmaeil negad (جغرافیا و توسعه, 2017)
Climatic changes and environmental degradation has had a significant impact on the movement of people around the world. Reactions of people is different in  response to the climatic  changes and the most important  reaction of people is toward the  environmental deterioration  and removal of the relocation risk, that migrations caused by climatic changes and its consequences form the shape of climate refugee. The idea of Climatic refugee or climatic change refugee is a relatively new idea.  Lack of adaptability and the required capacity for climatic changes  are the most important causes of the humans vulnerability. Southern Khorasan Province located  in the southeast of Iran is one of the places vulnerable to climatic changes. In this study to assess the climatic changes, the precipitation and  temperature data  and the  number of days of dust and groundwater resources have been used for 20 years up to 2014. To identify and predict the climatic changes of South Khorasan province, Statistical Down Scaling Model (SDSM) by using LARS- WG model and Evaluation Indices of climatic changes have been used. For the assessment, the climatic changes of 10 stations of the province for period 2010-2030 have been made under Lars Model. By using such data, firstly ,the centers of the crisis due to the climatic changes have been identified and zoned in GIS environment. Then the dispersion of the settlements which are subject to such risks has been specified. For the assessment of climatic refugees, the migration statistics of year 1996 and up to 2011 have been used and the rural settlements at these areas which have been evacuated and removed in this period have been determined. Processing of climatic data shows that most of the  province districts were affected by climatic changes, but south of the province centered by Nehbandan, has had the greatest impacts of climatic changes. These events led to population displacement and the formation of climatic refugees in the south of the province and the population of the southern provinces has moved to the north of the province. The human settlements of the province in 1996 was equal to 61.76  percent which decreased  to 45.61  percent in 2011. So that the role of climatic changes in the last 20 years is evident with the  challenges such as drought, degradation of water resources, desertification, particularly in the west and south part of the province.